(untitled) (Muara Nada: Jurnal Pendidikan Seni, 2026)
Medo singing is one of the cultural heritages and traditional musical arts of the Udiworowatu Village community, Keo Tengah District, Nagekeo Regency, which plays an important role in the traditional peo-making ceremony. This song is an integral part of the Peo planting procession, functioning as a collective medium of expression to convey gratitude, respect for ancestors, and hopes for the safety and welfare of the community. In practice, Medo is not only sung as a form of ritual but also becomes an educational and spiritual medium that strengthens the cultural identity of the Keo community. In addition to being used in the context of making Peo, this song is also present in various other traditional moments, such as the construction of traditional houses and welcoming guests of honor, making it an important element in the social and religious life of the local community.